Nafas.Co: Pico Paint / Mohd Najib Kamarudin ...[et al.] - Kamarudin, Mohd. Najib; Nik Mohd Azlin Shah, Nik Ahmad Faisal; Khairil Anuar, Arif Amani Anwar; Mohamad Razali, Sahim Wafiy; Mohamed Saadun, Muhamad Azrul Aizad (2016)
Our company sells Pico Paint to reduce burden that students facing while doing their project. Our project is made up from a mixture of 50 ml of acrylic paint with 50 ml of water which widely used to spray paint onto small surface area object.